Evidence-based recommendation on toothpaste use - Jaime Aparecido Cury; Livia Maria Andaló Tenuta (Sociedade Brasileira de Pesquisa Odontológica, 2014)
Toothpaste can be used as a vehicle for substances to improve the oral health of individuals and populations. Therefore, it should be recommended based on the best scientific evidence available, and not on the opinion of authorities or specialists. Fluoride is the most important therapeutic substance used in toothpastes, adding to the effect of mechanical toothbrushing on dental caries control. The use of fluoride toothpaste to reduce caries in children and adults is strongly based on evidence, and is dependent on the concentration (minimum of 1000 ppm F) and frequency of fluoride toothpaste use (2'/day or higher). The risk of dental fluorosis due to toothpaste ingestion by children has been overestimated, since there is no evidence that: 1) fluoride toothpaste use should be postponed until the age of 3-4 or older, 2) low-fluoride toothpaste avoids fluorosis and 3) fluorosis has a detrimental effect on the quality of life of individuals exposed to fluoridated water and toothpaste. Among other therapeutic substances used in toothpastes, there is evidence that triclosan/copolymer reduce dental biofilm, gingivitis, periodontitis, calculus and halitosis, and that toothpastes containing stannous fluoride reduce biofilm and gingivitis.